2021
DOI: 10.1371/journal.ppat.1009495
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid oxidation participates in resistance to nutrient-depleted environments in the insect stages of Trypanosoma cruzi

Abstract: Trypanosoma cruzi, the parasite causing Chagas disease, is a digenetic flagellated protist that infects mammals (including humans) and reduviid insect vectors. Therefore, T. cruzi must colonize different niches in order to complete its life cycle in both hosts. This fact determines the need of adaptations to face challenging environmental cues. The primary environmental challenge, particularly in the insect stages, is poor nutrient availability. In this regard, it is well known that T. cruzi has a flexible met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The endogenous energy reserve present in various evolutive forms of T. cruzi has been attributed to carbohydrates [19]. However, while epimastigotes can interchange glucose and amino acids, they also can accumulate fatty acids into lipid droplets during growth and use this reserve to support its growth after glucose exhaustion [13,48,49]. Furthermore, this same study demonstrated that the insect stages coordinate the activation of fatty acid consumption with the metabolism of glucose [48].…”
Section: Discussionmentioning
confidence: 98%
“…The endogenous energy reserve present in various evolutive forms of T. cruzi has been attributed to carbohydrates [19]. However, while epimastigotes can interchange glucose and amino acids, they also can accumulate fatty acids into lipid droplets during growth and use this reserve to support its growth after glucose exhaustion [13,48,49]. Furthermore, this same study demonstrated that the insect stages coordinate the activation of fatty acid consumption with the metabolism of glucose [48].…”
Section: Discussionmentioning
confidence: 98%
“…The effects observed on processes related to carbohydrate and amino acid-dependent energy production in epimastigotes are like those reported after nutritional stress induced by long periods of starvation. Souza et al evaluated the role of FA oxidation after depriving T. cruzi epimastigotes cultures of glucose, finding that, in the absence of glucose, lipid droplets become the main sources of FA, which help the body survive nutritional stress by producing acetyl-CoA that fuels TAC, contributing to mitochondrial ATP production ( Souza et al, 2021 ). In summary, epimastigotes use FA as carbon and energy source when glucose and amino acids are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, triatomine guts and feces contain a diverse range of chemical classes, with lipids the most abundant [11,27]. Free fatty acids are an important energy source for T. cruzi epimastigotes, if glucose is limiting, and are sufficient to induce T. cruzi development from epimastigotes to metacyclic trypomastigotes [28][29][30]. Purines and pyrimidines are present and may serve as sources for parasite proliferation.…”
Section: The Triatomine Vector and Metabolites: Four-way Interactions...mentioning
confidence: 99%